UJI KETELITIAN HASIL KOREKSI GEOMETRIK CITRA SATELIT ALOS PRISM DENGAN HITUNG PERATAAN KUADRAT TERKECIL METODE PARAMETER - Bambang Sudarsono; Atriyon Julzarika (Diponegoro University, 2010)
Remote sensing is a branch science of Geodesy Engineering that using satellite applications for survey andmapping. One of the natural resources satellite that be used for mapping is Alos Satellite.It is own of Japan, italso could be used in 3D Application, especially Prism and Palsar. There are some methods for making 3Dapplication that are stereo mode, interferometry, and DSM2DEM. Geometric correction of this satellite is veryimportant so it needs a study for its statistical test. Alos satellite have 3D shape as Digital Terrain Model(DSM), not Digital Terrain Model (DTM), Digitallen HöheModellen (DHM), Digital Geoid Model (DGM) orDigital Elevation Model (DEM). Alos satellite that be used are Alos Prism where it has spatial resolution in 2.5meter. The reference system of 3D model that are produced by Alos satellite image still as surface for z axis, forx axis and y axis has been closed to 2D reference system in some certain datum and system of map projection.So, this research will give result of its accuracy and precision and it could uses for the reference system.For its statistical test, it needs a method for checking its accuracy. It is least square adjustment in parametermethods. In case, it needs a research for observate the accuracy and precision of Alos satellite data using aleast square adjustment of parameter methods. Data from Alos satellite will be compared with data from Globalpositioning System (GPS) of geodetic. The results of this research will be used as reference for next research toinvent a way for changing DSM from satellite, radar, air video and interferometry-automatically.